O efeito do treinamento resistido no tratamento da sarcopenia em idosos: uma revisão sistemática - MORAES, Caio Gabriel Alves (2022)
This study is a systematic review of what studies related to the health of the elderly point out on the influence of resistence training on the quality of life of these subjects in the treatment and prevention of sarcopenia, which is the loss of muscle mass, strength and power due to age, being a natural process of aging. With the inscrease in the number of elderly in Brazil, form approximately 9,8% in 2005 to 14,3% in 2015, according to the censos of IBGE. Some factors such as decreased levels of steroid hormones, protein intake, increased pro-inflamatory citokines and physical inactivity during life and old age contribute to the acceleration and worsening of this process, despite most of the mechanisms responsible for sarcopenia are not fully clear, this phenomenon cause, in elderly, indisposition, body unbalance, loss of strength, power, functional disability and, due to these factors, can lead to more serious consequences, such as accicents, loss of autonomy, among other things. Demonstrably, as we will address throughout the present review, resistance trainig is shown as a determining fator in strength and muscle power gain, quality of life and less dependence of other people, by the elderly. The regular practice of physical exercises may be able to promote benefits to the elderly at various levels: morphological, neuromuscular, metebolic and psychological, serving both for prevention and treatment of agerelated diseases.